TERTIARY EDUCATION - ONE OF THE MAJOR EUROPE 2020 OBJECTIVES - TASCOVICI, Daliana (Annals of Spiru Haret University. Economic Series, 2019)
The present paper speaks about the changes the Romanian system of learning suffers. Under these circumstances of social, political, economic and cultural changes and challenges, the pre-university and university system of learning have to cover several forms and situations, namely those high school graduates without the baccalaureate diploma. The case study under analysis revealed some unexpected pieces of information referring to the young undergraduates’ vulnerabilities and degree of information and implication in their own future.